High-speed rail's impact on the location of office employment within the Dutch Randstad area - Jasper Willigers; Han Floor; Bert Van Wee (European Regional Science Association (ERSA), 2005)
With the upcoming implementation of high-speed railway infrastructure in the Netherlands, interest has arisen in the spatial-economic effects this might have. Experiences with high-speed rail outside the Netherlands have shown that effects at a local or regional level can be important, due to relocation of employment within regions and cities. This paper focuses on this issue by presenting the results of discrete choice models for office location choice. Both stated choice data and revealed choice data are used. The discrete location choice models give information on to what extent the introduction of high-speed rail in the Netherlands can change the attractiveness of individual cities within the Randstad area on the one hand and of places within these cities on the other hand. As accessibility is an important concept in this topic, attention is given to the specification of accessibility indicators. Hereby, distinction is made between centrality and connectivity. Centrality refers to the position of a location within the transport network and relative to possible origins and destinations. Potential accessibility indicators based on a spatial interaction model are used to represent centrality. Connectivity refers to how well a location is connected to a transport network. Indicators for connectivity are for example the distance to the nearest railway station or motorway access ramp and also the level-of-service provided, such as the train frequency at a station. Furthermore, the paper focuses on a segmentation of employment that reflects this paper's purpose of studying the influence of (high-speed) rail on location choices. Whereas accessibility by car is relevant for location choices of all types of office employment, accessibility by rail in general and accessibility by high-speed rail in particular seem important to more distinct groups of office employment.
Keywords: 330